Diseases of ear, nose and throat head and neck surgery - Dhingra, P.L (Elsevier, 2014)
Diseases of Ear, Nose and Throat is a popular textbook of ENT. The first edition of the book was published in 1992. Since then it has received wide acceptance from the readers and every attempt has been made to update the current edition in the light of the advances made by the speciality.